Discursive Influence in the Professional Speech Activity of an Individual Psychologist - Kalmykov, George (East European Journal of Psycholinguistics, 2017)
Abstract. The study is focused on such psycholinguistic issues: sphere of psychological activity that is predominantly of discursive nature and is based on the use of speech influence methods, design of discourses as implementation of applied psychological needs of a psychologist in his professional speech activity; highlighting of various discursive possibilities impacts associated with various aspects of its organization and effects, specific types of discourses in certain operating conditions of the therapist and psycho adviser. Here is considered changing consciousness and behavior of human individual potential of psychological impact of a discourse and the ability of character to carry out speech intervention in mental regulators of life, existence and interaction with others in the social space; the discourse is regarded as born by a psychologist concept that states social relations, image of “I” and “Others”, forms the social identity, perceptions, judgments, instructions, converts not adaptive and inappropriate patterns of behavior, rigid stereotypes of human consciousness to adaptive and creative ones radically changing the old and forming the new meanings; are given separated by the author of the article examples of different types of discourses, namely discourse explanation, imperfect discourse, transfer discourse, genetic interpretation discourse, reinterpretation discourse, I-discourse, restart discourse, reidentification discourse, discourse of self-expression of feelings here and now.ЛітератураReferences1. Бьюдженталь Д. Искусство психотерапевта. М.: Издательство «Корвет», 2011. Bugental, J. (2011). Iskusstvo Psihoterapevta [The Art of the Psychotherapist]. Moscow:Korvet.Вайнер И. Основы психотерапии. Пер. с англ. Е. Антоновой, В. Белоусова. СПб. :Питер, 2002.Weiner, I. (2002). Osnovy Psihoterapii [Principles of Psychotherapy]. S.-Petersburg: Piter.Gray P. Ego аnd Analysis оf Defense. Aronson, Jason Inc., 1994.Gray, P. (1994). Ego аnd Analysis оf Defense. Aronson, Jason Inc.Hill C. & O’Brien K. (1989). Helping Skills: Facilitating Exploration, Insight andAction. Washington, DC: American Psychological Association.Джонсон С. Практика эмоционально-фокусированной супружеской терапии.Создание связей. М. : Научный мир, 2013.Johnson, S. (2013). Praktika Emotsionalno-Fokusirovannoy Supruzheskoy Terapii.Sozdanie Svyazey. [Practice of Emotionally Focused Conjugal Therapy. Creating Links].Moscow: Nauchnyiy Mir.Дискурс в современном мире. Психологические исследования / под. ред. Н.Д. Павловой и Н. А. Зачесовой. М.: Издательство «Институт психологи РАН», 2011.Discurs v Sovremennom Mire. Psihologicheskiye Issledivaniya [Discourse in ModernWorld. Psychological Studies]. (2011). D. Pavlova, N. Zachosova, (Eds). Moscow:Institute of Psychology of the Russian Academy of Sciences.Калина Н. Ф. Анализ дискурса в психотерапии// Психологический журнал. 2000.Т. 21, №2. С. 100–107.Kalina, N.F. (2000). Analiz diskursa v psihoterapii [Discourse analysis in psychotherapy].Psihologicheskiy zhurnal, 2(21), 100–107.Калина Н.Ф. Основы психоанализа. К. : Реф-бук-Ваклер, 2001.Kalina, N.F. (2001). Osnovy Psihoanaliza [The Foundations of Psychoanalysis]. Kyiv:Refl-buk.Калмыкова Е. С., Мергенталлер Э. Нарратив в психотерапии: рассказы пациентов оличной истории // Психологический журнал. 1998, №5. С. 97–104.Kalmykova, E. S. & Mergentaller, E. (1998). Narrativ v psihoterapii: rasskazyi patsientovo lichnoy istorii [Narrative in psychotherapy: stories of patients about personal history].Psihologicheskiy Zhurnal, 5, 97–104.Калмиков Г.В. Дискурсивні практики як компоненти професійно-мовленнєвоїдіяльності психологів// Психолінгвістика. Психолингвистика. Psycholinguistics:[зб. наук. праць ДВНЗ «Переяслав-Хмельницький державний педагогічнийуніверситет імені Григорія Сковороди»]. Переяслав-Хмельницький: ФОПДомбровська Я. М. 2016. Вип. 20(1). С. 98–111.Kalmykov, G. V. (2016). Diskursivni praktiki yak komponenti profesiyno-movlennevoyidiyalnosti psihologIiv. [Discursive practices as components of psychologists’professional speech activity]. Psiholingvistika, 20(1), 98–111.Калмиков Г. В. Дискурс як мовленнєвий вплив// Психолінгвістика.Психолингвистика. Psycholinguistics: [зб. наук. праць ДВНЗ «ПереяславХмельницький державний педагогічний університет імені Григорія Сковороди»].Переяслав-Хмельницький: ФОП Домбровська Я. М. 2017. Вип. 21(1). С. 112–128.Kalmykov, G. V. (2017). Dyskurs yak movlennjevyi vplyv [Discourse as a speechinfluence]. Psykholingvistyka, 21(1), 112–128.Кейсмент П. Обучение на наших ошибках. Алматы: Дарын, 2005.Keysment, P. (2005). Obuchenie na Nashih Oshibkah [Learning from Our Mistakes].Almaty: Daryn.Коттлер Д. Совершенный психотерапевт. Работа с трудными клиентами. СПб.:Питер, 2002. Kottler, D. (2002). Sovershennyi Psihoterapevt. Rabota s Trudnyimi Klientami [ThePerfect Psychotherapist. Working with Difficult Clients]. S.-Petersburg: Piter.Кубрак Т. А. Интенция самопрезентации субъекта в вербальной коммуникации:Автореф. дис.... канд. психол наук: 19.00.01. М, 2009.Kubrak, T.A. (2009). Intentsiya samoprezentatsii sub’ekta v verbalnoy kommunikatsii[The intention of the subject of self-presentation in verbal communication]. Extendedabstract of Ph.D. dissertation. Moscow.Orlinsky, D. E., Grawe, K., & Parks, B. K. (1994). Process and Outcome inPsychotherapy. In: Handbook of Psychotherapy and Behavior Change, (pp. 270–378). A.E. Bergin & S. L. Garfield (Eds.), New York: Wiley.Павлова Н.Д. Коммуникативная функция речи: интенциональная и интерактивнаясоставляющие: Автореф. дис.... д. психол. наук. М., 2000.Pavlova, N. D. (2000). Kommunikativnaya funktsiya rechi: intentsionalnaya iinteraktivnaya sostavlyayuschie [The communicative function of speech: intentional andinteractive components]. Extended abstract of Doctoral dissertation. Moscow.Роджерс К. Необходимые и достаточные условия терапевтических личностныхизменений / К. Роджерс // Журнал практического психолога. 2012, №1. С. 8–25.Rogers, K. (2012). Neobhodimyie i dostatochnyie usloviya terapevticheskih lichnostnyihizmeneniy [Necessary and sufficient conditions of therapeutic personality change].Zhurnal Prakticheskogo Psihologa, 1, 8–25.Россохин А. В., Петровская М. Б. Имплицитные содержания психоаналитическогодиалога: экспертные возможности компьютерной психолингвистики//Психологический журнал. 2001. Т. 22, №6. С. 77–86.Rossohin, A.V. & Petrovskaya, M.B. Implitsitnyie soderzhaniya psihoanaliticheskogodialoga: ekspertnyie vozmozhnosti kompyuternoy psiholingvistiki [The implicit contentsof psychoanalytic dialogue: the expert possibilities of computer psycholinguistics].Psihologicheskiy Zhurnal, 6(22), 77–86.Соколова Е. Т., Бурлакова Н. С. К обоснованию метода диалогического анализаслучая // Вопросы психологии. 1997, №2. С. 61–76.Sokolova, E. T. & Burlakova, N. S. (1997). K obosnovaniyu metoda dialogicheskogoanaliza sluchaya [The substantiation of the method of dialogical analysis of the case].Voprosy Psihologii, 2, 61–76.Соммерз-Фланаган Д., Соммерз-Фланаган P. Клиническое интервьюирование. 3-еизд. М.: Диалектика. 2006.Sommerz-Flanagan, D. & Sommerz-Flanagan, R. (2006). Klinicheskoe Intervyuirovanie[Clinical Interviewing]. Moscow: Dialektika.Стренгс Д. Интерпретативные треугольники Давенлу в работе с образом Бога //Консультативная психология и психотерапия. 2000., №2. C. 155–171.Strengs, D. (2000). Interpretativnyie treugolniki Davenlu v rabote s obrazom [Terpretivetriangles Davanloo in working with the image of God]. Konsultativnaya psihologiya iPsihoterapiya, 2, 155–171.Энрайт Д. Гештальт, ведущий к просветлению. СПб.: Центр гуманистическихтехнологий «Человек», 1994.Enright, J. (1994). Geshtalt, Veduschiy k Prosvetleniyu [Enlightening Gestalt]. S.-Petersburg: Chelovek.Ягнюк К. В. Анатомия терапевтической коммуникации. Базовые навыки итехники : учебное пособие. М.: Когито-Центр. 2014.Yagnyuk, K. V. (2014). Anatomiya Terapevticheskoy Kommunikatsii. Bazovyie Navyki iTehniki [Anatomy of Therapeutic Communication. Basic Skills and Techniques].Moscow: Kogito-Tsentr.Ялом И. Дар психотерапии. М.: Изд-во Эксмо, 2005.Yalom, I. (2002). Mamochka i Smysl Zhizni: Psihoterapevticheskie Istorii [Momma andthe Meaning of Life: Tales of Psychotherapy]. Moscow: Eksmo.Ялом И. Мамочка и смысл жизни: психотерапевтические истории. М.: ЭКСМОПресс, 2002.Yalom, I. (2005). Dar Psihoterapii [The Gift of Psychotherapy]. Moscow: Eksmo-Press.
Keywords: discourse; discursive impact; professional-speech activity; different types of discourse.